Pengaruh Penambahan Paladium Terhadap Perilaku Thermal Amalgam Tembaga Tinggi Tipe Lathe Cut - Ellyza Herda (Faculty of Dentistry, Universitas Indonesia, 2015)
Effects of additing 1 percent (w/o) palladium (Pd) on the thermal behavior of a lathe cut type high copper amalgam (13 w/o copper) were studied. The identical alloys, with and without 1% Pd were fabricated. X-ray diffraction studies of the amalgams revealed the elimination of the γ2-phase by Pd addition DSC thermogram of non-Pd containing amalgam indicated the existence of two γ1-phaseone with the transition temperature (endothermic peak) at 88◦C and the other at 109◦C. The thermogram data of the Pd containing amalgam showed an endothermic peak at 110.7◦C. The transition temperature of the n phase of the palladium containing amalgam is 4.9◦C lower than the transition temperature of the n phase of the non Pd containing amalgam. This result indicates that the n phase of the Pd containing amalgam includes more of Tin (Sn) than the non-Pd containing amalgam. The thermogravimetri diagram showed that the phase decomposition occurred at about 390◦C for the non-Pd containing amalgam and at about 410◦C for the Pd containing amalgam. It is concluded that the addition of 1% Pd into a lathe cut type of high copper amalgam (13%) could eliminate the formation of γ2 phase as well as an unstable γ1 phase, promoting strong mercury bonding to Silver.